Metallic Glasses Properties and Processing - Huang, Hu (IntechOpen, 2018)
Metallic glasses are very promising engineering and functional materials due to their unique mechanical, chemical, and physical properties, attracting increasing attention from both scientific and industrial communities. However, their practical applications are greatly hindered due to three main problems: dimensional limit, poor tension plasticity, and difficulty in machining and shaping. Therefore, further investigation of these issues is urgently required. This book provides readers with recent achievements and developments in the properties and processing of metallic glasses, including mainly thermoplastic forming of metallic glasses (Chapter 2), atomic-level simulation of mechanical deformation of metallic glasses (Chapter 3), metallic glass matrix composites (Chapter 4), and tribo-electrochemical applications of metallic glasses (Chapters 5 and 6).